Unicystic Ameloblastoma of Posterior Maxilla- a Rare Entity! - Iqbal, Sana (International Journal of Pathology, 2020)
Unicystic ameloblastoma is an uncommon odontogenic lesion, with radiographic and gross appearance suggestive of a jaw cyst. Microscopic features of the lesion, however, reveal classic ameloblastic type lining of the cyst cavity with or without mural nodular growth. Unicystic ameloblastoma typically presents in the posterior mandibular region, in the second decade of life. We report a case of unicystic ameloblastoma in the posterior mandibular region which is a rare site for this lesion. In this case report, 40 years old male presented to the Maxillofacial Department with a history of swelling at the upper 1st premolar region extending to the 3rd molar region. Orthopentogram (OPG) showed a radiolucency and root resorption of the1stand 2nd molar and impacted third molar of the maxilla. This was followed by cone-beam computed tomography (CBCT). The patient was treated by surgical enucleation of the lesion and conjoint extraction of impacted 3rd molar. The microscopic picture was consistent with unicystic ameloblastoma.